Стан медичної освіти США на початку ХХ ст. - Куліченко, Алла Костянтинівна; Куличенко, А. К.; Kulichenko, A. (Суми: СумДПУ, 2018)
У статті увагу зосереджено на стані медичної освіти США на початку ХХ ст. Зокрема, представлено педагогічні ідеї Ф. Біллінгза щодо покращення медичної освітньої парадигми та погляди А.Флекснера щодо тогочасної ситуації у медичній освіті. Також з’ясовано, що в Америці окрім алопатичних медичних шкіл (навчальних закладів традиційної медицини) існували приватні (комерційні) та сектантські медичні школи. До останніх належали гомеопатична, еклектична, фізіомедична та остеопатична школи. У дослідженні подано коротку характеристику зазначених сектантських медичних шкіл (за А.Флекснером). В статье внимание сосредоточено на состоянии медицинского образования США в начале ХХ в. В частности, представлены педагогические идеи Ф. Биллингса касательно улучшения медицинской образовательной парадигмы и взгляды А. Флекснера о ситуации в медицинском образовании. Также установлено, что в Америке кроме аллопатических медицинских школ (учебных заведений традиционной медицины) существовали частные (коммерческие) и сектантские медицинские школы. К последним принадлежали гомеопатическая, эклектическая, физиомедицинская и остеопатическая школы. В исследовании дана краткая характеристика указанных сектантских медицинских школ (по А. Флекснеру). In the early 20th century, American medical education experienced severe crises and needed upgrading. Many US medical professionals and educators offered their views concerning future reforms, with F. Billings, and A. Flexner among them. For his part, F. Billings proposed many important pedagogical decisions to address the existing problems in education, and two options of duration of medical education - six years and seven years. Moreover, F. Billings and A. Flexner considered proprietary and sectarian medical schools to be a future challenge for the American medical education. Such educational establishments were found for profit and authority. Additionally, these educational establishments practiced such doctrines as homeopathy, eclecticism, physiomedicine, osteopathy, etc., as opposed to allopathic medicine. The aim of the paper is to highlight the situation in the American medical education in the early 20th century, particularly to focus on proprietary and sectarian medical schools. In this paper, the author deals with such methods as heuristic and bibliographic ones - to identify and systematize historical and pedagogical literature concerning the research; biographical method - to study and analyze the content of F. Billings's and A. Flexner's pedagogical views on to the situation in the American medical education in the early 20th century; pedagogical reconstruction - to reproduce historical and pedagogical reality due to the functioning of proprietary and sectarian medical schools. According to A. Flexner, there were four types of sectarian medical schools: homeopathic, eclectic, physiomedical, and osteopathic ones. It should be stressed thatsectarian medical schools were the first medical educational establishments that trained women. Nevertheless, proprietary and sectarian medical schools had weak points, such as lack of unification in terms of entry requirements, poor material and technical base, abandoned and dirty buildings, incompetent academic staff, low tuition fee, almost no practical classes, insufficient clinical education, etc. These factors led to the closure of almost all proprietary and sectarian medical schools, with the osteopathic one being the exception. As for the prospects of further research, we are going to highlight the preconditions of the reform in the American medical education in the early 20th century, and to point out Flexner's recommendations in the context of the medical educational paradigm (based on the work "Medical education in the United States and Canada: a report to the Carnegie Foundation for the Advancement of Teaching", 1910).
Состояние медицинского образования США в начале ХХ в.
American medical education: situation in the early 20th century
Keywords: американська медична освіта; педагогічні погляди; Ф. Біллінгз; А. Флекснер; приватна (комерційна) медична школа; сектантська медична школа; гомеопати; еклектики; фізіомедики; остеопати; американское медицинское образование; педагогические взгляды; Ф. Биллингс; А. Флекснер; частная (коммерческая) медицинская школа; сектантская медицинская школа; гомеопаты; эклектики; физиомедики; остеопаты; American medical education; pedagogical views; F. Billings; A. Flexner; proprietary medical school; sectarian medical school; homeopathists; eclectics; physiomedicals; osteopaths